Synthesis and initial in vitro evaluation of PSMA-targeting ligands with a modified aromatic moiety at the lysine ε-nitrogen atom - Zyk, Nikolai Y.; Ber, Anton P.; Nimenko, Ekaterina A.; Shafikov, Radik R.; Evteev, Sergei A.; Petrov, Stanislav A.; Uspenskaya, Anastasia A.; Dashkova, Natalia S.; Ivanenkov, Yan A.; Skvortsov, Dmitry A.; Beloglazkina, Elena K.; Majouga, Alexander G.; et al. (Bioorganic & medicinal chemistry letters, 2022)
[Display omitted] We report an improved series of ligands targeting prostate specific membrane antigen (PSMA). The new compounds were designed by the introduction of changes in the structure of the aromatic fragment at ε-nitrogen atom of lysine that resulted in improved biological parameters. Some of them demonstrated high selectivity and nanomolar IC50 values. We synthesized and tested two conjugates with a fluorescent label Sulfo-Cy5 as an example of the use of the obtained PSMA inhibitors as a basis for the creation of diagnostic preparations.